Harapan pengunjung terhadap perbaikan fasilitas duduk Taman Flora Surabaya - Detyo Campoko (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2018)
Taman Flora Surabaya is one of Surabaya garden that have so many visitors. Having various facilities that can be utilized various circle, this garden has a shortage of design elements of physical seating facilities. This study discusses the opinion of active and rare visitors of Taman Flora Surabaya about how to improvement of sitting facilities. The method used is descriptive qualitative, by respondent opinion technique. The result of the research shows that: 1) active visitors have hope that the facility of Taman Flora Surabaya should be repaired immediately; 2) Jembatan Surabaya is chosen by various stakeholders as icon of sitting facility design to improvement Taman Flora Surabaya.Keywords: visitor, sitting facility, Taman Flora Surabaya.